Nipple-sparing mastectomy with different approaches: surgical incisions, complications, and cosmetic results. Preliminary results of 100 consecutive patients at a single center. Issue 12 (December 2018) - Corso, G.; De Lorenzi, F.; Vicini, E.; Pagani, G.; Veronesi, P.; Sargenti, M.; Magnoni, F.; Naninato, P.; Maisonneuve, P.; Sangalli, C.; Rietjens, M.; Galimberti, Viviana
Summary: Nipple- and areola-sparing mastectomy is a novel surgical approach that preserves the nipple–areolar complex. Patients with moderate and/or severe breast ptosis are usually not eligible for this surgical approach. In this study, we aimed to demonstrate the feasibility of nonconventional surgical approaches for nipple-sparing mastectomy. One hundred consecutive patients diagnosed with primary breast cancer (BC) were enrolled in this study. Clinical and pathological data such as body mass index, smoking status, breast ptosis, complications, and aesthetic satisfaction (Breast-Q test) were collected. According to different types of breast ptosis, surgical procedures were classified as (a) hemi-periareolar, (b) round block, (c) vertical pattern, and (d) wise pattern skin incisions. We performed statistical analysis to assess the correlation with complications, degree of ptosis, and breast-Q scores. Among the 117 surgical procedures performed in 100 patients with BC, no significant associations are verified considering clinical and pathological data, complications, pre- and postsurgery satisfactions, and other parameters. Different surgical approaches represent the evolution of "classic" nipple-sparing mastectomy, thus meeting the cosmetic and oncological results. These procedures are safe and also indicated in cases conventionally considered as not eligible for nipple–areola preservation.